The Influence of Digital Platforms on Operational Performance through Service Process Capabilities with Digital Culture as a Moderation Variable at BPJS Employment Branch Offices - Baharudin, Ardi; Tricahyo , Dodie (International Journal Labs, 2025)
Digital transformation has become a major driver in improving organizational efficiency and effectiveness, including in public sector institutions such as BPJS Ketenagakerjaan. As a public agency responsible for delivering social security services to workers, BPJS Ketenagakerjaan is required to provide services that are fast, accurate, efficient, and accessible at any time. In this context, the implementation of integrated digital service platforms serves as a strategic tool to enhance service quality and strengthen public accountability. This study aims to analyze the influence of Digital Service Platforms on Operational Performance, with Service Process Capability as a mediating variable and Digital Culture as a moderating variable. A quantitative approach was employed, using the Structural Equation Modeling – Partial Least Square (SEM-PLS) method for data analysis. The unit of analysis is the organization, specifically 121 Branch Offices (Cabang Induk) of BPJS Ketenagakerjaan selected through purposive sampling. The results of this study are expected to provide theoretical contributions to the development of literature on public sector digitalization, and practical implications for BPJS Ketenagakerjaan in formulating strategies to strengthen process capabilities and digital culture in support of improved operational performance. The findings may also serve as a reference for similar public organizations in implementing strategic digital transformation initiatives.